FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PEMBELIAN IMPULSIF - Topan Siswanto; Komang Hanita; I Nengah Arsana (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
This study aims to determine the partial and simultaneous effect of promotion, shopping emotion, and store atmosphere on impulse buying behavior at Transmart Carrefour Mataram City. The population in this study were consumers who visited the Transmart Carrefour Mataram City with a total sample of 100 respondents. The sampling technique used in this study is a non-probability sampling technique with purposive sampling method. The data analysis technique used is the multiple linear regression analysis technique. The results of this study indicate that the variables of promotion, shopping emotion, and store atmosphere do not partially have a significant effect on impulsive buying behavior, only shopping emotion, and store atmosphere which has a significant effect, while promotion has an insignificant negative effect and simultaneously shows that the variables of promotion, shopping emotion, and store atmosphere have a significant effect on impulsive buying behavior. In addition, the store atmosphere variable has the most dominant influence on impulse buying.